2000
DOI: 10.1038/sj.ejcn.1600999
|View full text |Cite
|
Sign up to set email alerts
|

A developmental view of the undernourished child: background and purpose of the study in Pangalengan, Indonesia

Abstract: Objectives: This is the ®rst of a series of reports published in this supplement of an experimental study to test the validity of a conceptual model about the intellectual delay of undernourished children. This paper describes the model and outlines its empirical and theoretical basis. The model provides a conceptual framework for the multiple relationships among growth and developmental domains presumably affected by malnutrition. It allows for a statistical statement regarding the goodness of ®t between data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 53 publications
1
36
0
7
Order By: Relevance
“…The present study on play behavior utilized a subsample of 55 children recruited for a larger experimental study (Pollitt, 2000;Pollitt et al, 2000a). Play observations began later in the data collection period of the larger study.…”
Section: Methodsmentioning
confidence: 99%
“…The present study on play behavior utilized a subsample of 55 children recruited for a larger experimental study (Pollitt, 2000;Pollitt et al, 2000a). Play observations began later in the data collection period of the larger study.…”
Section: Methodsmentioning
confidence: 99%
“…Lucas et al 18 stress that malnourished children are from poor population groups with high child mortality and parents who are less equipped to care for and stimulate their children. Major improvements in child development have been evidenced in settings with adequate health, nutrition, and stimulation 39,40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional rehabilitation in early life has nearly always produced salutary changes with the exception of those children who had experienced iron de®ciency anemia (IDA) during infancy and the toddler years. Many studies have shown that the delay in mental development observed among children having suffered from IDA during the ®rst two years of life was not corrected by iron repletion therapy (Lozoff, 1991;Pollitt, 2000). In addition, early IDA with and without iron treatment has been associated with later mental retardation and learning disabilities (Hurtado et al, 1999;Pollitt, 1999) and with poor performance in tests of intelligence, andaor speci®c cognitive processes later in school (Lozoff et al, 2000).…”
Section: Introductionmentioning
confidence: 99%